The Impact of Emotional Intelligence on Teamwork Skills in Public Schools Principals - Fakhrou, Abbulnaser A.; Moarbes, Laba; Rjeily, Christelle Abou; Essa, Mohammed (Advances in Social Sciences Research Journal, 2022)
This study aimed to identify the level of emotional intelligence and its impact on the cooperative work skills of public school principals, as well as examining the levels of their cooperative work skills practices. And its relationship to gender variables, and administrative experience. The study sample consisted of 53 public school principals, and the descriptive analytical approach was adopted in data collection, analysis and interpretation. The results showed that school principals had moderate levels of emotional intelligence, with a decrease in the abilities of emotional awareness, assertiveness and public relations. The study also revealed an average level of cooperative work skills practice, with low levels of empowerment skills practice. There are no statistically significant differences in the average emotional intelligence and the level of practice of cooperative work skills for the school principal due to the variables of gender and administrative experience. While there were statistically significant differences in the ability to adapt due to the gender variable for school principals. The results showed differences in the areas: the ability to withstand stress, control emotions, conflict resolution skills, communication and meeting management, attributed to the variable of administrative experience in favor of more experienced school principals. The study confirmed the existence of a positive and moderate correlation between emotional intelligence and collaborative work skills.